Smith, Pat and Lloyd. A video clip describing when the transporting of pre-fabricated building caused damage to the family home in Heart's Content. - Wilson, Lisa (2013)
Pat and Lloyd Smith discuss the Smith family home and some unusual damage that occurred to the front of the building.